Developmental but not adult cannabinoid treatments persistently alter axonal and dendritic morphology within brain regions important for zebra finch vocal learning - Gilbert, Marcoita T. (2014)
Prior work shows developmental cannabinoid exposure alters zebra finch vocal development in a manner associated with altered CNS physiology, including changes in patterns of CB(1) receptor immunoreactivity, endocannabinoid concentrations and dendritic spine densities. These results raise questions about the selectivity of developmental cannabinoid effects: are they a consequence of a generalized developmental disruption, or are effects produced through more selective and distinct interactions with biochemical pathways that control receptor, endogenous ligand and dendritic spine dynamics? To begin to address this question we have examined effects of developmental cannabinoid exposure on the pattern and density of expression of proteins critical to dendritic (MAP2) and axonal (Nf-200) structure to determine the extent to which dendritic vs. axonal neuronal morphology may be altered. Results demonstrate developmental, but not adult cannabinoid treatments produce generalized changes in expression of both dendritic and axonal cytoskeletal proteins within brain regions and cells known to express CB(1) cannabinoid receptors. Results clearly demonstrate that cannabinoid exposure during a period of sensorimotor development, but not adulthood, produce profound effects upon both dendritic and axonal morphology that persist through at least early adulthood. These findings suggest an ability of exogenous cannabinoids to alter general processes responsible for normal brain development. Results also further implicate the importance of endocannabinoid signaling to peri-pubertal periods of adolescence, and underscore potential consequences of cannabinoid abuse during periods of late-postnatal CNS development.